THE EFFECT OF TALKING STICK MODEL ON STUDENTS’ SPEAKING ABILITY (A STUDY AT THE ELEVENTH GRADE STUDENTS OF SMA NEGER 1 PADANG BOLAK JULUIN 2020/201 ACADEMIC YEAR) - MUHAMMAD RASID SIREGAR (JURNAL LINER (Language Intelligence and Educational Research), 2020)
Abstract: The objective of this research is to know whether there is a significant effect of Talking stick model on students’ speaking ability at the eleventh grade students of SMA Negeri 1 Padang Bolak Julu in 2020/2021 Academic Year. This research uses experimental method with pre-experimental research design; one group pretest-posttest design. The population is all of the eleventh grade students which consists of 96 students. Technique sampling that is used on this research is systematic sampling and the number of the samples are 32 students. In collecting the data, the researcher uses observation sheet to get the data of the application of impromptu speaking method and test to get the data of the students’ speaking ability. The researcher uses statistic process in analyzing the data by using ttest formula. Based on the data that had been analyzed, the result of data analyzing showed that ttest is higher than ttable (ttest 15.41> ttable 2.04). So, the hypothesis is accepted. It means that there is a significant effect of Talking stick model on students’ speaking ability at the eleventh grade students of SMA Negeri 1 Padang bolak julu in 2020/2021 Academic Year. Keywords:Talking stick model, speaking ability.